2019
DOI: 10.1097/md.0000000000017332
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram to predict overall survival and disease-specific survival with appendiceal mucinous adenocarcinoma

Abstract: To predict the survival of appendiceal mucinous adenocarcinoma (AMA) by prognostic nomogram.A total of 3234 patients with AMA were collected from the Surveillance, Epidemiology, and End Results (SEER) database from 1973 to 2015. Univariate and multivariate Cox proportional hazards (PH) regression analyses were used to generate independent prognostic factors. These variables were included in the nomogram to predict overall survival (OS) and disease-specific survival (DSS) at 1-, 3-, and 5- years. These data are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Several obvious advantages can be found in this study compared with previous studies that established appendiceal cancer nomograms. First of all, we are the first to build nomograms specifically for the survival of patients with appendiceal cancer after surgery, while the previous nomograms did not specifically serve postoperative patients and was limited to mucinous adenocarcinoma (Xie et al 2016;Yan et al 2019). Furthermore, compared to the previous two studies which only included 1404 and 3234 patients (Xie et al 2016;Yan et al 2019), our nomogram was based on a larger data study, which included 5945 patients, and was validated in 1982 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several obvious advantages can be found in this study compared with previous studies that established appendiceal cancer nomograms. First of all, we are the first to build nomograms specifically for the survival of patients with appendiceal cancer after surgery, while the previous nomograms did not specifically serve postoperative patients and was limited to mucinous adenocarcinoma (Xie et al 2016;Yan et al 2019). Furthermore, compared to the previous two studies which only included 1404 and 3234 patients (Xie et al 2016;Yan et al 2019), our nomogram was based on a larger data study, which included 5945 patients, and was validated in 1982 patients.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, we are the first to build nomograms specifically for the survival of patients with appendiceal cancer after surgery, while the previous nomograms did not specifically serve postoperative patients and was limited to mucinous adenocarcinoma (Xie et al 2016;Yan et al 2019). Furthermore, compared to the previous two studies which only included 1404 and 3234 patients (Xie et al 2016;Yan et al 2019), our nomogram was based on a larger data study, which included 5945 patients, and was validated in 1982 patients. Second, we included more commonly used prognostic factors in clinical practice compared with previous nomograms, such as preoperative CEA, chemotherapy and tumor size, which means that the prognosis of patients with appendiceal cancer can be more accurately predicted.…”
Section: Discussionmentioning
confidence: 99%
“…The documented rate of LN+ in MAC is variable and there have been equivocal findings as to whether mucinous histology is itself an independent risk factor of LN+ 22‐24 . To our knowledge, no study has investigated the risk factors of LN+ in patients with MAC, though previous investigations evaluating all patients with appendiceal cancers (adenocarcinomas and neuroendocrine tumors) have shown that grade is strongly associated with increased rates of LN+ and worse survival outcomes 2,14,15,23,24 . LN+ is often considered less common in MAC; this study identifies an appreciable rate of LN+ among all MAC patients and a particularly high rate of LN+ in certain subgroups.…”
Section: Discussionmentioning
confidence: 67%
“…MAC has one of the lowest LN+ rates of all appendiceal neoplasms, varying from 4% to 20% in the current literature 2,7,14‐16 . Even among patients with MAC having peritoneal dissemination, the risk of LN+ is 6% in low‐ to moderate‐grade disease, but rises to 29% among high‐grade disease patients 12 .…”
Section: Introductionmentioning
confidence: 94%
“…Previous large population-based studies have identified key demographic and clinical prognostic factors associated with survival in patients with appendiceal malignancies, including age, race, marital status, histological type, tumour stage, tumour grade, lymph node resection, chemotherapy and surgical intervention 1 4–10. These variables have been used to construct prognostic nomograms that predict overall mortality and disease-specific survival 11 12…”
Section: Introductionmentioning
confidence: 99%